A RESEARCH ON ENTREPRENEURAL LEVEL OF SOCIAL MEDIA USERS ON BITCOIN AND CRYPTO CURRENCIES - SÜTCÜ, CEM SEFA; AYTEKİN, ÇİĞDEM (ISTANBUL KULTUR UNIV, 2018)
Thanks to the new global order established after the Second World War and the communication networks that have become widespread. Due to this, the electronic payment systems that have started to be used since the second half of the 20th century in the world and the credit cards called plastic money have started to be widely used in our country since the 80 '. From the beginning of 2000's, it is observed that cash-based transactions are lagging e-money-based transactions. Since the beginning of the 90's the Internet and social media emerged with new media technologies and after 2004, it has become a dominant idea that these environments provide freedom and even create disorder. In the last 5-6 years we have seen the trade of crypto currencies like Bitcoin. Bitcoin is a method of payment that people use for their purchases based on mutual trust, without an authority issuing it. It works independently of the state authority and the banking system. From this point of view, it is seen as the reflection of freedom originally envisaged for the internet environment. In this context, the question of how bitcoin systems are perceived, and the level of entrepreneurship are issues that needs to be investigated. In this study, a survey was conducted to measure the level of entrepreneurship of bitcoin miners, buyers and sellers. Twitter users were selected for the sample. The research is designed to examine the impact of entrepreneurship motivated by investors' interest in entering the arena that is said to be quite new and risky, and which sub-factors may dominate, which deals with bitcoin and similar crypto currencies. The findings show that users who are interested in mining, buying-selling and trading have very high level of entrepreneurial points.
Keywords: Bitcoin; Crypto Currency; Entrepreneurship; Social Media; CRYPTOCURRENCIES